KAJIAN TEORITIS TENTANG ZAKAT TEMBAKAU DALAM PERSPEKTIF ISLAM:: Study Kasus di Desa Peresak Kecamatan Sakra, Kab. Lombok Timur - SARNI (AL-RASYAD: JURNAL HUKUM DAN ETIKA BISNIS SYARIAH, 2023)
This paper discusses tobacco zakat from an Islamic perspective. The author uses qualitative research methods with observation and interviews as a tool to obtain data. After conducting a long research, the authors found that the community, especially in Peresak Village, Sakra District, in issuing zakat on the results of their tobacco farming, they issued zakat on the results of the tobacco trade in accordance with what was explained by Allah in the Al-Quran regarding zakat on agricultural products, although many say that zakat on tobacco agricultural products is makruh, but the Peresak Village Community adheres to the Islamic shari'ah that already applies, even though their tobacco products have exceeded the obligatory zakat limit/exceeding the nishab, what they zakat is the result of the tobacco trade, so they also issue zakat. , to help the lives of the poor around him. The people of Peresak Village, Sakra District, equate their tobacco farming products with other plants besides tobacco plants so they pay zakat from their tobacco farming products, with the aim of cleansing themselves from heinous and stingy deeds and to cleanse their souls from sinful acts. Tobacco agricultural products are equated with other agricultural products, and are qiyaskan into the results of the trading business (tijaroh) so that the results of the tobacco trading business must pay zakat.